Performance Evaluation of Seismic Isolation System by Installation Location in Lighthouse Structures - Moo-Won Hur; Tae-Won Park (Shock and Vibration)
The purpose of this study is to evaluate the applicability of seismic isolation devices for marine accidents under seismic loads. The lighthouse structure is a very important facility when the ship approaches the port. However, it is necessary to reinforce the structure to protect it from earthquake. This study presents isolation technology as a method to enhance the seismic performance of lighthouse structures built before seismic design criteria were established. This paper analyzed improvement of seismic performance in three cases of seismic isolation by applying the proposed method of isolation technology. In Case 1, the entire lighthouse structure is isolated, and in Case 2, only the lighthouse lens, the most important component of the lighthouse structure, has been isolated to assure constructability and economy. In Case 3, isolation effect was analyzed by comparing Case 1 and Case 2 with lighthouse structures.